The ecohydrology framework. Bibliometric network analysis and literature review - Nardi , Margherita; Aricò, Salvatore; Buonocore, Elvira; Franzese, Pier Paolo (Ecological Questions, 2025)
In the context of increasing environmental stressors, Ecohydrology represents an interdisciplinary and comprehensive framework useful to ensure the sustainable management of water resources, mitigating risks to both anthropic and ecological systems. This research examines the milestones of Ecohydrology through a Bibliometric Network Analysis and literature review, emphasizing its possible integration with Ecosystem and Environmental accounting. In particular, it explores how the Ecohydrological perspective can support researchers, local managers, policy-makers and other stakeholders in building climate-resilient cities. A total number of 3335 articles were analysed using the VOSviewer software to perform a bibliometric network analysis. Three thousand one hundred articles were screened for the literature review. Then, 719 were selected through cross-reference and their abstracts were reviewed. Finally, 290 full text articles were reviewed and data were extracted from 36 articles. Key findings highlight the urgent need to study the interplay between hydrological processes and water-related ecosystem services for addressing the mounting challenges posed by human activities and the resulting climate change. The main objective of this field of science is to comprehend and mitigate the effects of land use changes on water and to forecast the impact of climate change on ecosystems and water supply. Bibliometric network maps reveal limited research on the convergence of Ecohydrology, Ecosystem accounting, and Environmental accounting, indicating the need for further research and collaborative efforts to overcome this knowledge gap. Lastly, ecological and socioeconomic considerations are crucial in water-related management, as economic growth and human well-being are intricately linked to water resources and healthy ecosystems. Addressing these challenges and ensuring sustainable water management require cooperation among ecohydrologists, other scientists, stakeholders, and decision-makers. Integrating the ecohydrological perspective into ecosystem accounting is essential to facilitate dialogue among different disciplines and better adapt to climate change.